An initial assessment of employee capital plans - Dawidowicz, Dawid (Wstępna ocena pracowniczych planów kapitałowych, 2019)
The pension system in Poland is an example of the implementation of many reforms and changes, some of which are contradictory. The purpose of the article was the initial assessment of employee capital plans (PPK) as an element supplementing the third pillar of the pension system. The paper is of a theoretical and empirical nature. The study uses comparative analysis and the cluster method to evaluate the investment policy pursued by defined date funds (FZD). The study proves that the investment policy of the funds is similar and that three dominant investment policies can be distinguished. The extended payback period for PPK fund management institutions increases the risk of withdrawing the offer of some financial institutions in the future. The assessment of the PPK scheme allows to state that this program may increase the retirement savings of Poles. The author postulates also the need to increase the knowledge of market participants in terms of both the need to save for retirement and in the forms of saving
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 7, s. 5-17
Keywords: population ageing; employee capital plans; pension system; starzenie się społeczeństwa; pracownicze plany kapitałowe; system emerytalny